ARTISTIC ACHIEVEMENT OF KAROL (LUKASH) HUBEL IN LIUBESHIV PIARIST CHURCH OF SAINT JOHN THE EVANGELIST IN VOLYN 60s XVIII CENTURY - SHERETIUK, Ruslana (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2025)
The article is devoted to the little-studied issue in domestic humanities of the artistic achievement of the outstanding artist of late Baroque (middle – second half of the XVIII century), the monk of the Roman Catholic order of Piarists Karol (Lukash) Hubel. He spent the whole his creative life in the Liubeshiv Order Center in Volyn, actively establishing the artistic visions of western European art. It is argued, that since the Liubeshiv Piarist Church was destroyed during the Soviet era, the unique paintings of Karol Hubel were also lost. That is why, it is justified to explore his artistic heritage in more detail. The research methodology is based on the general scientific principles of analysis and synthesis, systematization, and generalization. At the same time, it relies on special scientific methods, namely on problem-thematic, chronological, art history, as well as systemic and structural. The scientific novelty of the studio lies in the exploration of the artistic acquisition of the order of Piarists in Volyn, in particular, returning from forgetfulness the name of a famous artist Karol (Lukash) Hubel, understanding his creative work, and significance in the context of the development of Ukrainian culture. It is revealed, that monumental painting by Karol (Lukash) Hubel in Church of St. John the Evangelist in Liubeshiv, Volyn, take a special place in his creative heritage. Here, taking into account the entire artistic arsenal of the late Baroque era, wall fresco compositions were created by him, as well as picturesque altars and decorative images of illusionistic niches. It is characterized, that they had delicacy, originality of plots, perfect technical implementation, naturalness and harmony in the interpretation of figures, dramatic pathos, depth of religious feelings, as well as unique coloristic. By the scale of work, that was done, and artistic skills, the monumental painting of the Church of St. John the Evangelist, executed by Karol Hubel, during the 60s XVIII century, became a pearl of European late Baroque art. It is concluded, that the artistic achievements of Karol (Lukash) Hubel in the Church of St. John the Evangelist in Liubeshiv became a great contribution to the artistic activity of the Order of Piarists in Volyn, a brilliant manifestation of the artistic achievements of the late Baroque era and at the same time – an invaluable acquisition of Ukrainian culture.